Evolutionary history of host use, rather than plant phylogeny, determines gene expression in a generalist butterfly. Issue 1 (December 2016) - Celorio-Mancera, Maria; Wheat, Christopher; Huss, Mikael; Vezzi, Francesco; Neethiraj, Ramprasad; Reimegård, Johan; Nylin, Sören; Janz, Niklas
Abstract Background Although most insect species are specialized on one or few groups of plants, there are phytophagous insects that seem to use virtually any kind of plant as food. Understanding the nature of this ability to feed on a wide repertoire of plants is crucial for the control of pest species and for the elucidation of the macroevolutionary mechanisms of speciation and diversification of insect herbivores. Here we studiedVanessa cardui, the species with the widest diet breadth among butterflies and a potential insect pest, by comparing tissue-specific transcriptomes from caterpillars that were reared on different host plants. We tested whether the similarities of gene-expression response reflect the evolutionary history of adaptation to these plants in theVanessa and related genera, against the null hypothesis of transcriptional profiles reflecting plant phylogenetic relatedness. Result Using both unsupervised and supervised methods of data analysis, we found that the tissue-specific patterns of caterpillar gene expression are better explained by the evolutionary history of adaptation of the insects to the plants than by plant phylogeny. Conclusion Our findings suggest thatV. cardui may use two sets of expressed genes to achieve polyphagy, one associated with the ancestral capability to consume Rosids and Asterids, and another allowing the caterpillar to incorporate a wide range of novel host-plants.